A pragmatic protocol for characterising errors in atmospheric inversions of methane emissions over Europe. Issue 1 (1st January 2021) - Szénási, Barbara; Berchet, Antoine; Broquet, Grégoire; Segers, Arjo; Denier van der Gon, Hugo; Krol, Maarten; Hullegie, Joanna J.S.; Kiesow, Anja; Günther, Dirk; Petrescu, Ana Maria Roxana; Saunois, Marielle; Bousquet, Philippe; et al.
Abstract: This study aims at estimating errors to be accounted for in atmospheric inversions of methane (CH4 ) emissions at the European scale. Four types of errors are estimated in the concentration space over the model domain and at selected measurement sites. Furthermore, errors in emission inventories are estimated at country and source sector scales. A technically ready method is used, which is implemented by running a set of simulations of hourly CH4 mixing ratios for 2015 using two area-limited transport models at three horizontal resolutions with multiple data sets of emissions and boundary and initial conditions as inputs. The obtained error estimates provide insights into how these errors could be treated in an inverse modelling system for inverting CH4 emissions over Europe. The main results show that sources of transport errors may better be controlled alongside the emissions, which differs from usual inversion practices. The average total concentration error is estimated at 29 ppb. The assessed error of total CH4 emissions is 22% and emission errors are heterogeneous at sector (23–49%) and country scales (16–124%), with largest errors occurring in the waste sector due to uncertainties in activity data and emission factors and in Finland due to uncertainties in natural wetland emissions.